ANTHROPIC PRINCIPLE AND PHILOSOPHY OF COSMISM: ONTOLOGICAL AND ETHICAL ASPECTS - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The anthropic principle is one of the principles of modern cosmology around which, from the last decades of the XXth century and so far, constantly occur ideological discussions, not only scientific, but also philosophical. Aim and tasks: The paper studies metaphysical aspects of cosmological and philosophical discussions over the Cosmos understanding as a “human-sized” world system in the context of “strong” anthropic principle. The author, besides, draws on the theoretical views of the philosophers of Russian cosmism, namely V. Vernadsky, K. Tsiolkovsky, A. Chizhevsky. Tasks: to analyze philosophical-ontological and moral-ethical aspects of the role of man and consciousness in the development of matter. Research methods: Philosophical analysis is carried out on the basis of the materialist approach and the principles of dialectics. The procedure of critical comprehension of the given concepts and estimations is applied. Results. The expediency in the anthropic picture of the world is argued not to be correlated with the anthropocentrism and idealistic teleology. At the same time, the naturalism views of evolutionists over the essence of consciousness and man is criticized. The author does not agree with the reducing of consciousness to the cerebral material activity, on the one hand, and of the consciousness hypostatization, its ontologization, on the other. Also grounds that the essence of intelligent life is based on purposeful character of activity and on freedom from natural determinism in its development. Moral and ethical imperatives of human activity in its earthly and cosmic purpose are analyzed as well. Discussion. The author believes that the development of an anthropic picture of the world drives science to the adoption of humanitarian concepts. The human life is determined not only in scientific and technical activity, but also in a moral along broad sense. The development of science and technology within of immoral social and political landmarks of a person can ruinously affect both human affairs on Earth and space ones. Conclusion. The metaphysics of the anthropic cosmic principle and the ideas of Russian anthropocosmist philosophers form a single field of theoretical reflection. On the author opinion, modern ideas in quantum cosmology about the role of an observer in the Universe and the ethic's orientations of Russian cosmic philosophy converge in natural-philosophical hypothesis of E. Ilyenkov.